SYNTACTICAL REPETITION ON SELECTED POEMS OF MAYA ANGELOU - Anna Riana Suryanti Tambunan; Maria Silaban; Rika Haloho; Priskila Nainggolan; Olivia Rizki; Rahmat Eko; Ryo Tauhid (LINGUISTICA, 2020)
The aim of this research is to find out the syntactical repetition on selected poems by Maya Angelou namely Still I Rise, Caged Birds, Alone and Woman Work. The technique of collecting the data was to download the selected poems.  The data were analyzed  and found four repetition that he said . The repetition is Anaphora, Epiphora, Framing, and Anadiplosis.  Our research found that the repetition used to stress the author’s goals on her poem.  It can be make people remember her intention in her poem. Keywords: Stylistic,  repetition,  poem